Sosialisasi Digital Marketing Dalam Upaya Meningkatkan Income Anggota Dwp Upt Psda Ws Brantas Di Kediri - ISTIASIH, HERMIN (Universitas Nusantara PGRI Kediri, 2022)
Digital marketing is the marketing of products or services using digital technology, The focus of this paper is on conceptual understanding of digital marketing and the purpose of the PKM is to help partners use social media to market their products. Partners in this PKM are members of the DWP UPT PSDA WS Brantas in Kediri. The partner’s problem is the lack of knowledge in marketing their products, especially the use of digital marketing. The PKM team conveyed digital marketing socialization so that it could increase family income. The socialization method used is lecture, question and answer, and simulation. The target to be achieved in this PKM is the socialization of digital marketing in an effort to increase the income of DWP members so that they become prosperous families and increasing the empowerment of partners and the ability to take advantage of marketing opportunities through digital marketing.